Diagnosis of tuberculosis pleurisy with three endoscopic features via pleuroscopy. (February 2021) - Lee, Chung-Shu; Li, Shih-Hong; Chang, Chih-Hao; Chung, Fu-Tsai; Chiu, Li-Chung; Chou, Chu-Liang; Wang, Chih-Wei; Lin, Shu-Min
Background: Tuberculosis (TB) is a constant threat even with a worldwide active public health campaign. Diagnosis of TB pleurisy is challenging in the case of pleural effusion of unknown origin after aspiration analysis. The study was designed to demonstrate a simple image interpretation technique to differentiate TB pleurisy from non-TB pleurisy using semi-rigid pleuroscopy. Methods: The study retrospectively enrolled 117 patients who underwent semi-rigid pleuroscopy from April 2016 to August 2018 in a tertiary hospital. We analyzed the possibility of TB pleurisy using three simple pleuroscopic images via semi-rigid pleuroscopy. Results: Among 117 patients, 28 patients (23.9%) were diagnosed with TB pleurisy. Sago-like nodules/micronodules, adhesion, and discrete distribution were noted in 20 (71.4%), 20 (71.4%), and 19 (67.9%) patients with TB pleurisy, respectively. Sago-like nodules/micronodules, adhesion, and discrete distribution were noted in six (6.7%), 37 (41.6%), and no (0.0%) patients with non-TB pleurisy, respectively. The positive and negative predictive values of any two out of three pleuroscopic patterns for TB pleurisy were 100.0% and 93.7%, respectively. Conclusions: A high positive predictive value for TB pleurisy was demonstrated by the presence of any two out of the three characteristic features. Absence of all three features had an excellent negative predictive value for TB pleurisy. Our diagnostic criteria reconfirm that pleuroscopic images can be used as predictors for TB pleurisy in patients with undiagnosed pleural effusion. The reviews of this paper are available via the supplementary material section.